2003
DOI: 10.1509/jmkr.40.4.468.19391
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Interaction of Auditory and Visual Advertising Elements with Chinese and English

Abstract: Multimedia advertisements often contain nonverbal auditory elements, such as music and sound effects, and nonverbal visual elements, such as images and logos. On the one hand, these elements can have the unintended negative effect of interfering with the processing of the verbal ad copy. Two experiments demonstrate that auditory elements interfere more with the learning of and cognitive responding to English ad copy than with Chinese ad copy, and vice versa for visual elements. On the other hand, auditory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 55 publications
4
75
0
Order By: Relevance
“…Past research has found non-verbal auditory cues to interfere more with message processing when paired with English rather than Chinese advertisement messages-likely due to the fact that alphabetical languages rely more on auditory processing and the subvocalizing of words, while logographic languages depends more on visual processing (Tavassoli & Lee, 2003). Given that music has been shown to carry semantic meaning (Koelsch, et al, 2004), a possibility is that this interference effect of music on alphabetical language processing will be reduced if the meaning of the music is congruent with the focal advertisement message (i.e., the taste of the advertised product).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has found non-verbal auditory cues to interfere more with message processing when paired with English rather than Chinese advertisement messages-likely due to the fact that alphabetical languages rely more on auditory processing and the subvocalizing of words, while logographic languages depends more on visual processing (Tavassoli & Lee, 2003). Given that music has been shown to carry semantic meaning (Koelsch, et al, 2004), a possibility is that this interference effect of music on alphabetical language processing will be reduced if the meaning of the music is congruent with the focal advertisement message (i.e., the taste of the advertised product).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Previous research has, for example, investigated the role of visual factors (An, 2007;Zhou, Zhou, & Xue, 2005) and music (Murray & Murray, 1996;Tavassoli & Lee, 2003) in advertising across different cultures. While prior studies focused on musical surface features (e.g., genre or the meaning of lyrics; Murray & Murray, 1996; presence vs. absence of music; Tavassoli & Lee, 2003), the present study extends this line of research by investigating how meaning that is encoded in the very musical structure is differentially perceived across cultures. Our findings may also have implications for the processing of advertising messages:…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Over the last two decades an emerging stream of research has emerged that has provided somewhat qualitative overviews of China (Garten, 1998;Kao, 1993;Lieberthal & Lieberthal, 2003;Vanhonacker, 1997), Chinese buying behavior (Ackerman & Tellis, 2001;Graham & Lam, 2003;Klein, Ettenson, & Morris, 1998;Sun, Chen, Fang, & Liang, 2000;Tavassoli & Lee, 2003;Zhou & Nakamoto, 2001), and the fundamentals of business and marketing compared with Western practices (Atuahene-Gima & Li, 2002;Fang, Palmatier, & Evans, 2004;Song, Xie, & Dyer, 2000;Yan, 1998;Zeng & Williamson, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In their discussion of television advertising disclosures, Hoy and Andrews (2004) note that Tavassoli and Lee's (2003) finding that processing differences for alphabetic (e.g., English) versus logographic (e.g., Asian) languages has implications for disclosures. Specifically they noted that Tavassoli and Lee (2003) found that, with English speakers, audio distractions interfered more with learning and retrieving advertising text compared to visual distraction.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically they noted that Tavassoli and Lee (2003) found that, with English speakers, audio distractions interfered more with learning and retrieving advertising text compared to visual distraction. The opposite effect was found for Chinese speakers where visual distraction was a hindrance.…”
Section: Discussionmentioning
confidence: 99%